2003
DOI: 10.1002/tcr.10063
|View full text |Cite
|
Sign up to set email alerts
|

The repetitive C‐terminal domain of RNA polymerase II: Multiple conformational states drive the transcription cycle

Abstract: RNA polymerase (RNAP) II is a complex multisubunit enzyme responsible for the synthesis of mRNA in eukaryotic cells. The largest subunit contains at its C-terminus a unique domain, designated the CTD, comprised of tandem repeats of the consensus sequence Tyr(1)Ser(2)Pro(3)Thr(4)Ser(5)Pro(6)Ser(7). This repeat occurs 52 times in mammalian RNAP II. The CTD is subject to extensive phosphorylation at specific points in the transcription cycle by distinct CTD kinases that phosphorylate certain positions within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…The C-terminal domain (CTD) is composed of 52 tandem repeats of heptapeptide YSPTSPS that are subject to phosphorylation. The two major phosphorylation sites of Pol II are Ser2 and Ser5; phosphorylation at these sites results in two forms of Pol II (hypophosphorylated IIa and hyperphosphorylated IIo) (28). In the process of transcription initiation, the predominant phosphorylation of Pol II is on Ser5, while in transcription elongation, the major form is Ser2 phosphorylation (9).…”
mentioning
confidence: 99%
“…The C-terminal domain (CTD) is composed of 52 tandem repeats of heptapeptide YSPTSPS that are subject to phosphorylation. The two major phosphorylation sites of Pol II are Ser2 and Ser5; phosphorylation at these sites results in two forms of Pol II (hypophosphorylated IIa and hyperphosphorylated IIo) (28). In the process of transcription initiation, the predominant phosphorylation of Pol II is on Ser5, while in transcription elongation, the major form is Ser2 phosphorylation (9).…”
mentioning
confidence: 99%
“…Each repeat contains two potential Ess1 binding sites (underlined). The heptad repeat within the CTD of Rpb1 is known to be reversibly phosphorylated in vivo, and these changes in phosphorylation are correlated with distinct steps in pol II transcription (initiation, elongation, and termination) and mRNA processing (capping, 3Ј cleavage, and polyadenylation (22,23)). Our genetic analyses, and those of Hani and colleagues, have shown that Ess1 is involved in multiple stages of transcription and mRNA processing (16,25,26,47 We have proposed a model in which Ess1 binds and isomerizes the CTD of Rpb1, thereby affecting cofactor binding to the pol II complex (16).…”
mentioning
confidence: 99%
“…Furthermore, extensive CTD phosphorylation in response to UV exposure has been proposed to reduce transcription initiation on an undamaged target gene in vitro, possibly by decreasing the pool of RNAPII competent for preinitiation complex assembly (24). The later observation may reflect the proposed dual role of CTD kinases, which is to act either as a specific positive transcription factor or in some circumstances as a general negative factor (25).…”
mentioning
confidence: 99%